THE PROBLEM OF THE RELATIONSHIP BETWEEN THEORETICAL AND EMPIRICAL THINKING - Denysenko, Ye. (Pedagogy of Higher and Secondary Education, 2010)
The article reveals some aspects of theoretical and empirical thinking and the question of their correlation opens up.